Program Everyday Untuk Mengembangkan Akhlak Mulia Anak Usia 5-6 Tahun - Rofiqoh, Rofiqoh; Samawi, Ahmad; Anisa, Nur (UIR PRESS, 2024)
The everyday program is one of the habituation programs that is carried out every day to develop children's noble character but, in its implementation there are still some children who do not concentrate, play, and talk to themselves. The purpose of the research is to describe, find out the inhibiting and encouraging factors, and find out the impact of the everyday program to develop noble morals. The method used is qualitative with a case study approach. The results of this study concluded that the description of the everyday program is a program of habituation to read short letters in tartil interspersed with the cultivation of morning aqidah which aims to make children have a basic Islamic religion and recognize short letters from an early age. This program is a superior activity that is supported by the safari dhuha program, the Friday clean program, and environmental love activities. Supporting factors of this program include educators, evaluation, reward and punishment, motivation, follow-up, and infrastructure. While the inhibiting factors include the community environment, family environment, and internal factors. The impact of the everyday program is to increase love for the Qur'an, increase the skill of reading the Qur'an, especially in tajweed, increase faith in Allah SWT by worshiping, and have an impact on noble character because children are always accustomed to doing good things such as attitude, speech, and actions so that they can make good traits and character for children.